2006
DOI: 10.1063/1.2173051
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed metal clusters in solid matrices: A new experimental setup

Abstract: We describe a new experimental setup for the production of samples of metal clusters embedded in matrices stable at ambient conditions. The cluster ions are generated in the gas phase and codeposited fragmentation-free together with the evaporated matrix. Mean cluster sizes range from a few to many thousands of atoms. For small clusters (n < 20) mass selection is possible, larger clusters are deposited in narrow size distributions. Matrix materials include metals (Cu, Ag) and oxides such as quartz. The perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The experimental setup is described in detail elsewhere 24 and is only sketched briefly. Cobalt cluster ions are generated in the gas phase using a homebuilt magnetron cluster source ͑based on the principle introduced by Haberland et al 25 ͒ and guided by ion optics through several differential pumping stages toward the deposition chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup is described in detail elsewhere 24 and is only sketched briefly. Cobalt cluster ions are generated in the gas phase using a homebuilt magnetron cluster source ͑based on the principle introduced by Haberland et al 25 ͒ and guided by ion optics through several differential pumping stages toward the deposition chamber.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously used this technique for samples with higher concentrations 24 and observed a blocking temperature of ϳ50 K as well as a coercive field of Ͼ500 Oe for a sample of Co clusters with ͗n͘ = 15 atoms at a concentration of 8 at. % in a copper matrix.…”
Section: ͑3͒mentioning
confidence: 99%
“…The experimental setup has been described elsewhere [11] and will only be sketched briefly. Atomic or cluster ions are generated in the gas phase in a magnetron cluster source following the design of Haberland et al [13].…”
Section: Methodsmentioning
confidence: 99%
“…Recently it was shown that also very small silver clusters of a few atoms only have intriguing properties and that their fluorescence is not only an ideal tool for fundamental researchers to determine their atomic and electronic structure [8,9] but that it might also be exploited in applications [10]. The aim of our research is to find means to produce samples of well defined metal clusters stabilized in protective matrices and to study their properties [11,12]. In this article we present a series of feasibility studies on the generation of tailor-made samples of metal clusters embedded in co-evaporated silica matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Samples are prepared according to the strategy of "clusterassembled materials" [12]. They consist of thin films of copper or silver in which are dispersed well-defined cobalt clusters.…”
Section: Methodsmentioning
confidence: 99%